(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
Data are now woven into every sector and function in the global economy, and, like other essential factors of production such as hard assets and human capital, much of modern economic activity simply could not take place without them. The use of Big Data — large pools of data that can be brought together and analyzed to discern patterns and make better decisions — will become the basis of competition and growth for individual firms, enhancing productivity and creating significant value for the world economy by reducing waste and increasing the quality of products and services. Big Data demand cost-effective, fault tolerant, scalable and flexible and innovative forms of information processing for decision making. This paper emphasis on the features, architectures, and functionalities of Big data, Hadoop,Map Reduce, HDFS.